Soil-foundation interaction model for the assessment of tunnelling-induced damage to masonry buildings. (January 2022) - Burd, H.J.; Yiu, W.N.; Acikgoz, S.; Martin, C.M.
Highlights: A simplified model is developed for tunnel-soil-building interaction problems. The soil response is represented by a nonlinear Winkler model. The soil-foundation model provides a good match with 3D finite element analysis. Frictional sliding at the soil-foundation interface is a significant mechanism. Abstract: Shallow tunnel construction inevitably causes local ground movements to occur. In an urban environment, these ground movements may cause damage to existing buildings on the ground surface. This paper describes a new, simplified, one-dimensional (1D) soil-foundation interaction model for use in damage assessment analyses of buildings that are at risk of tunnelling-induced damage. Simplified models of this sort facilitate efficient building risk assessments for urban infrastructure projects. The proposed soil-foundation interaction model is intended principally for buildings with traditional load-bearing masonry construction founded on embedded shallow foundations. A nonlinear Winkler model (incorporating shear and normal tractions acting on the foundation and the possibility of frictional sliding and gapping beneath the footing) is used to represent the soil-foundation interaction; the model also provides a means of specifying the tunnel-induced ground movements. The soil-foundation interaction model is demonstrated by combining it with a 2D plane stress model of a building facade; the combined model is shown to provide a close representation of the response of the facade to tunnel-induced ground movements, as computed with a corresponding 3D finite element model, but at a small fraction of the computational cost.